2017
DOI: 10.5958/0975-6906.2018.00005.6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Basmati rice genotypes with resistance to both bacterial blight and blast diseases using marker assisted restricted backcross breeding

Abstract: Marker assisted backcross breeding (MABB) is aimed at introgression of trait(s) into a popular variety to augment specific trait(s) in an otherwise popular variety. While MABB can improve a variety with respect to introgressed trait(s), it offers very little scope for improvement of other traits. Marker assisted restricted backcross breeding (MARBB) is an alternative which can help in identifying transgressive segregants especially, when the donor parent is an elite genotype with several desirable traits. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The shift in flowering duration under stress conditions in the present experiment indicates that water stress at the initiation of the reproductive stage affected flowering time. Similar results were reported by earlier studies [15,23,45,[49][50][51][52][53][54][55][56]. Bernier et al [9] and Venuprasad et al [16] reported that qDTY12.1 and qDTY3.1 influenced both grain yield and days to flowering under stress conditions, evincing that genes present within the QTLs are likely to be allied with early flowering.…”
Section: Agronomic Performance Of Pusa 44 Nils Under Stress and Non-ssupporting
confidence: 85%
See 1 more Smart Citation
“…The shift in flowering duration under stress conditions in the present experiment indicates that water stress at the initiation of the reproductive stage affected flowering time. Similar results were reported by earlier studies [15,23,45,[49][50][51][52][53][54][55][56]. Bernier et al [9] and Venuprasad et al [16] reported that qDTY12.1 and qDTY3.1 influenced both grain yield and days to flowering under stress conditions, evincing that genes present within the QTLs are likely to be allied with early flowering.…”
Section: Agronomic Performance Of Pusa 44 Nils Under Stress and Non-ssupporting
confidence: 85%
“…The performance of the NILs under unstressed situations proved that they recovered the maximum agronomic and grain quality attributes of Pusa 44 during the selection process. As successfully reported earlier [50][51][52][53], a stringent phenotypic selection along with marker-based background selection ensured an RPG recovery ranging between 98.6 and 99.4% after three successive backcrosses. This was further apparent from the recombinant selection data obtained later in the selection cycle, during the BC 3 F 4 stage, that indicated complete recovery of carrier chromosomes.…”
Section: Relative Drought Tolerance Of the Improved Nilssupporting
confidence: 68%
“…Therefore, marker assisted backcross breeding (MABB) was proven to be an efficient strategy for incorporation of desired trait associated genes/QTLs in numerous prominent rice varieties [21,42,43]. MABB along with stringent phenotypic selection was successfully employed for Basmati rice improvement for different biotic stresses [26,30,[44][45][46][47][48]. MABB is also proven to a superior method for QTLs transfer into desired cultivar/variety for different abiotic stresses as well, such as drought.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, marker assisted backcross breeding (MABB) was proven to be an efficient strategy for incorporation of desired trait associated genes/ QTLs in numerous prominent rice varieties [21,41,42]. MABB along with stringent phenotypic selection was successfully employed for Basmati rice improvement for different biotic stresses [43,44,45,25,46,29,47]. MABB is also proven to a superior method for QTLs transfer into desired cultivar/variety for different abiotic stresses as well, such as drought.…”
Section: Discussionmentioning
confidence: 99%